Acceptability of The Proposed Congestion Charging System in The Central Business District of Baguio City, Philippines - Lanigt, Ericka Renee A.; Samantela, Sandra S.; Devanadera, Ma. Catriona E.; Agaton, Casper Boongaling (UI Scholars Hub, 2025)
The City Government of Baguio is proposing a congestion charging system in the Central Business District (CBD) to address the ongoing issue of traffic congestion in the city. Although it is an effective tool, low public acceptability hinders its implementation. This study aims to assess Baguio City residents' acceptability regarding the CBD's congestion charging system. Specifically, it seeks to (1) identify the factors that influence residents’ acceptability of the proposed system, (2) evaluate whether there is a significant difference in acceptability across different road users (private vehicles, public transportation, cycling, and walking), and (3) provide recommendations for transportation policy planning in the CBD of Baguio City. The study employed an exploratory sequential design, using key informant interviews with four government officials and a perception survey involving 107 city residents. Survey results indicate that the proposed scheme is slightly unacceptable. Factors such as lack of information and awareness and perceived ineffectiveness reduce acceptability; however, revenue allocation may contribute to increased acceptance. Moreover, regardless of the mode of transportation, there is no significant difference in the level of acceptability or its influencing factors. Based on the low acceptability of the proposed system, the study recommends several transportation policy measures for the CBD of Baguio City: (1) policy packaging, (2) deployment of a pilot congestion charge, and (3) efforts to build public support through improved information and education campaigns, the establishment of information desks in barangays, and transparency in revenue allocation and management.